Using of a snap-through truss absorber in the attenuation of the sommerfeld effect - Godoy, W. R. A. de [UNESP]; Balthazar, J. M.; Pontes, B. R. [UNESP]; Felix, J. L. P. (E D P Sciences, 2012)
This work, considers a vibrating system, which consists of a snap-through truss absorber (STTA) coupled to an oscillator, under excitation of an DC motor, with an eccentricity and limited power, characterizing a non-ideal oscillator (NIO). It is aimed to use the absorber STTA, to establish the conditions, that we have the maxim attenuation of the jumpphenomenon (Sommerfeld Effect). Here, weare interestedin determining the conditions of the vibrating system, in which there arereduced amplitudes of the oscillator, when it passes through the region of resonance.